PENDIDIKAN AGAMA ISLAM BERBASIS IQ, EQ, DAN SQ - Samsul Bahri (Tarbawi, 2022)
This study aims to delve into the concept of Islamic Religious Education that integrates aspects of intellectual intelligence (IQ), emotional intelligence (EQ), and spiritual intelligence (SQ) within its curriculum. The employed methodology is a literature review, where data were collected through the examination of scholarly literature, including books, journals, and relevant electronic sources. Through content analysis, this research explores how Islamic Religious Education can be designed to develop not only students' academic abilities (IQ) but also emotional intelligence (EQ), comprising empathy and self-regulation, and spiritual intelligence (SQ) that stimulates a deeper search for meaning and purpose in life. The findings indicate that this integral approach can make a significant contribution to the holistic character formation of students, enabling them not only to succeed academically but also to flourish as empathetic individuals with strong spiritual resilience when facing life's challenges. This research provides new insights into the development of the Islamic Religious Education curriculum and recommends the implementation of IQ, EQ, and SQ concepts as key components in the educational process.